دور تطبيقات الذكاء الاصطناعي في تعزيز تنافسية المؤسسات الاقتصادية دراسة مجموعة من المؤسسات في ولاية الوادي - سويد مفيدة; رندة حداد; منال علال (جامعة الوادي University Of Eloued, 2025)
"هدفت هذه الدراسة إلى التعرف على دور تطبيقات الذكاء الاصطناعي في تعزيز تنافسية المؤسسات الاقتصادية من خلال دراسة ميدانية على مجموعة من المؤسسات التي تستخدم تطبيقات الذكاء الاصطناعي في نشاطها على مستوى ولاية الوادي. اعتمدت الدراسة على المنهج الوصفي التحليلي ودراسة حالة، واستخدمت الاستبيان كأداة رئيسية لجمع المعلومات من عينة من موظفي المؤسسات، حيث تم تحليل 47 استبياناً باستخدام برنامج SPSS، وتوصلت الدراسة إلى جملة من النتائج أبرزها انه توجد علاقة ذات دلالة إحصائية في الواقع لتأثير تبني تطبيقات الذكاء الاصطناعي على الميزة التنافسية للمؤسسات محل الدراسة. This study aimed to identify the role of artificial intelligence applications in enhancing the competitiveness of business organizations through a field study of a group of institutions that use artificial intelligence applications in their activities across the state of El Oued. The study relied on a descriptive analytical approach and a case study, and used a questionnaire as the primary tool for collecting information from a sample of enterprise employees. Forty-seven questionnaires were analyzed using SPSS. The study reached a number of results, the most notable of which is that there is a statistically significant relationship in reality between the impact of adopting artificial intelligence applications on competitive advantage
ماستر
Keywords: ذكاء اصطناعي، ابتكار، اتخاذ القرار، تنافسية المؤسسات; artificial intelligence; innovation; decision-making; corporate competitiveness